An Investigation of trends of Semantic Solutions for the Digital Libraries - Pandey, Shriram (Library Waves, 2015)
Paradigm shift from traditional digital library to social semantic digital library opens innovative and fresh possibilities to define digital library landscape. Contemporary digital library is not merely considered as a digitized collection with information management tools rather than digital library creates an environment to bring together collections, services, and people in support of the full life cycle of creation, dissemination, use, and preservation of data, information,and knowledge.